On how to achieve political significance from downwards: coca growers’ mobilizations in bolivia (1987- 2001) (2008)
This text presents a reflection about the coca growers’ mobilizations that have taken place in Cochabamba’s tropic between 1987 and 2001, analyzing the “structures of mobilization” that pheasant coca growers had by the time they mobilized against antidrug policy. In like manner, the article classifies the coca growers’ fights into different stages, characterizing each one according to the elements of confrontational political speech (for the case, of the coca growers and the government), the repertoires of confrontation, the State reactions, and the confrontation degrees, among other.